FAKTOR-FAKTOR PRODUK SIAP SAJI MEMPENGARUHI PERILAKU KEPUTUSAN KONSUMEN (Study Kasus Di Kota Yogyakarta) - Wendri Rusli; Retno Kurnianingsih; Ahmad Saefudin (Journal Competency of Business, 2017)
This research intent to measure factor’s success product that did by entrepreneur fast food at Yogyakarta passes trough spontaneous zoom yardstick buy. Factor success measurement product on obsevational in utiliizes analysis qualitative that gets bearing with price factor, availability of fast food, hygiene and taste to buyer decision. Utilizing bifilar Linear Regresion at deep obsevational it points out assess Constanta negative, meanwhile price, and availability of product, taste and constant hygiene. This observational result points out that after firm does assessment to perceive and hygiene as thing dominant.